A post-global financial crisis (GFC) framework for strategic planning, assessment and management decision making for US sustainable commercial real estate. Issue 6 (4th September 2017) - Christensen, Pernille Hoy
Abstract : Purpose: The purpose of this paper is to understand both the facts and the values associated with the breadth of issues, and the principles related to sustainable real estate for institutional investors. Sustainable real estate is a growing sector within the commercial real estate industry, and yet, the decision-making practices of institutional investors related to sustainability are still not well understood. In an effort to fill that gap, this research investigates the post-global financial crisis (GFC) motivations driving the implementation of sustainability initiatives, the implementation strategies used, and the predominant eco-indicators and measures used by institutional investors. Design/methodology/approach: This paper presents the results of a three-round modified Delphi study conducted in the USA in 2011-2012 investigating the nature of performance measurements and reporting requirements in sustainable commercial real estate and their impact on the real estate decision-making process used by institutional investors. Two rounds of in-depth interviews were conducted with 14 expert panelists. An e-questionnaire was used in the third round to verify qualitative findings. Findings: The key industry drivers and performance indicators influencing institutional investor decision making were associated with risk management of assets and whether initiatives can improve competitive market advantage. Industry leaders advocate for simple key performance indicators, which is in contrast to the literature which argues for the need to adopt common criteria and metrics. Key barriers to the adoption of sustainability initiatives are discussed and a decision framework is presented. Practical implications: This research aims to help industry partners understand the drivers motivating institutional investors to uptake sustainability initiatives with the aim of improving decision making, assessment, and management of sustainable commercial office buildings. Originality/value: Building on the four generations of the sustainability framework presented by Simons et al. (2001), this research argues that the US real estate market has yet again adjusted its relationship with sustainability and revises their framework to include a new, post-GFC generation for decision making, assessment, and management of sustainable real estate.